‘Religious Defence’ as an Element of Resistance to Change – in the Context of Family Counselling for Spouses in Crisis (addictions, violence) - Słowik, Margaret (Paedagogia Christiana, 2026)
In believing spouses in crisis, it is sometimes possible to observe the occurrence of ‘religious defence’ understood as resistance to change. It involves the functioning of certain psychological defence mechanisms that lead to specific, often inadequate interpretations of religious messages (such as ‘you have to bear your cross,’ ‘God alone is enough’ or ‘turning the other cheek’) in order to justify harming others or oneself. This article presents the results of a reflection on the central problem: What is ‘religious defence’ in spouses in crisis (related to the presence of addiction and/or violence problems) in the context of family counselling in its broadest sense for people with the above-mentioned problems? A method of literature analysis was used, and information gleaned from informal interviews with those involved in family counselling within the Catholic Church – both providing and benefiting from this type of support. The article finds that the ‘religious defence’ in spouses in crisis (related to the presence of addiction and/or violence problems) involves the use of religious arguments as a form of resistance to change. The manifestations of this defence focus on the spouses’ thinking and functioning in the following areas: perceptions of themselves and their own problem, understanding their participation in the marital crisis, (dis)understanding love as freedom-respecting and supportive of the good, (dis)understanding forgiveness, understanding the essence of sacramental marriage and the marriage vow in difficult situations, and understanding evangelical demands such as sacrificial love, bearing the cross, self-denial or turning the other cheek, etc. The same conviction or evangelical encouragement may be interpreted differently by each spouse, depending on individual motivations. Recommendations are formulated for family counselling to be more supportive in helping marriages in crisis (related to addiction and/or violence problems). The presented text can be considered as an introduction to qualitative research on the narrative of family counselling providers in the Catholic Church – strengthening and weakening the ‘religious defence’